Leadership Competences of Early Childhood Educators: The Mediating Role of Their Motivation - BADEA, Andreea-Luminița; SAVA, Simona (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2025)
Strong leadership competences among early childhood educators are essential to securing a formative learning environment in kindergarten. Such competences are developed by motivated teachers to continuously improve their didactic performance. The study aimed to investigate the relationship between leadership competences, specifically focusing on how these competences relate to preschool teachers’ motivation along their careers. 188 Romanian early childhood educators filled in two standardized instruments: the Teacher Leadership Scale (TLS) and the Teacher Motivation Questionnaire (TMQ). Data analysis using Spearman correlations, Kruskal-Wallis and Mann-Whitney U tests revealed a significant positive correlation between intrinsic motivation and leadership competences. We found significant differences by age groups, with younger teachers displaying lower leadership competence scores. Qualitative responses complemented the quantitative findings, highlighting professional development, communication improvement, and leadership support as key areas for enhancing leadership competences. The results suggest the need for differentiated training programs, tailored to teachers’ age and experience levels. Fostering intrinsic motivation, which emerged as a key driver for professional engagement and educational leadership development, should receive particular emphasis. The research provides insights for improving teacher development strategies in early childhood education and emphasizes the role of motivation to be fostered for promoting leadership growth.